China's Supply Chain Security Policy Content: X-Y Dual-Dimensional Analysis - Peng, Zhengxing; Deng, Lu; Xu, Penghao (International Journal of Social Sciences and Public Administration, 2024)
This article establishes a dual-dimensional X-Y analysis framework, examining policy tools (supply-side, demand-side, environmental) and policy objectives (addressing the "bottleneck" issue of core technology, improving the modernization level of the supply chain, perfecting the ecological system, promoting enterprise transformation and upgrading, and strengthening international cooperation). A coding analysis was conducted on 118 Chinese supply chain security policy texts within these dimensions.The results reveal imbalances in both policy tools and objectives, suggesting a need for further optimization and improvement. In response to this issue, the article recommends that the government coordinate planning, scientifically allocate policy tool combinations, clarify the synergistic relationships of each objective, and construct a comprehensive policy system. This research provides a novel and effective analysis framework and theoretical reference for optimizing supply chain security policies.